Analysis on thermodynamic and economic performances of supercritical carbon dioxide Brayton cycle with the dynamic component models and constraint conditions. (1st February 2022) - Liu, Zhiyuan; Wang, Peng; Sun, Xiangyu; Zhao, Ben
Abstract: Turbomachinery and heat exchanger are key components of the supercritical carbon dioxide (CO2 ) Brayton cycle system. It is of great necessity to investigate realistic cycle performance coupled with components characteristics. This paper analyzes the efficiency and economy of supercritical CO2 Brayton cycle based on the dynamic component models and constraint conditions. The parametric limits are compressor inlet temperature range from 305 K to 310 K, inlet pressure range from 7.4 MPa to 8.3 MPa, and maximum cycle pressure range from 15 MPa to 30 MPa. The results reveal that the achievable efficiency of a simple cycle is 0.13–0.62% points lower than theoretical maximum efficiency after considering constraint conditions. Meanwhile, the levelized cost of electricity (LCOE) under constraint conditions is 0.00038–0.00085/(kW·h) higher than the theoretical minimum LCOE. For a recompression cycle, constraint conditions have a more significant impact. The achievable efficiency of the cycle is 0.81–1.21% points lower than the maximum efficiency because of the constraints, and the available LCOE under constraint conditions is 0.0012–0.0018/(kW·h) higher than the theoretical minimum LCOE. Highlights: The supercritical CO2 cycle performance is investigated with the detailed component models. The component models are validated by current experimental or computational tests. The different feasible conditions are considered in the cycle-components coupled simulation. The impacts of feasible conditions on thermodynamic and economic performances are analyzed.